Urbanisme et environnement dans l’enseignement de l’architecture à la veille de Mai 1968 - Daniel Pinson (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Until 1967, urban planning was only one of the optional courses in the architecture section of the École nationale supérieure des beaux-arts (Ensba). The reform sought by André Malraux was intended to remedy this. During the course of wide-ranging preparatory meetings, the architect-urban planner Michel Écochard, who was entrusted with an unprecedented planning mission for Corsica, succeeded in defining the place of urban planning in its very aggressive proximity to the social sciences, as well as in its more premonitory proximity to the environment. The difficulties of coordination with the former, as well as internal tensions at Ensba, led to Michel Ecochard’s resignation, even before May 1968 broke out.